Analisis Akun Twitter Berpengaruh Terkait Serangan Cyber Bjorka menggunakan Metode Social Network Analysis - Adilla, Denise Sheryl; Mailoa, Evangs (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Twitter has become a social media for spreading and viewing the amount of information, such as information recently related to the data theft committed by Bjorka and has become quite a lively conversation on Twitter. The purpose of this research is to find out the most influential accounts related to Bjorka's popularity on social media. This study uses statistical methods of degree centrality, betweenness centrality, and closeness centrality. Based on the research conducted, there is an account that has the highest influence, @conversewhteold  with a degree centrality value of 122, betweenness centrality 0.000067, and a Closeness Centrality 1.0 also from the top 8 accounts, 7 of them tweets revealed that Bjorka had made false publications related to the theft what was done was even falsifying and selling data, then there was 1 account stating that the application made by the government for the public did not have data security guarantees.